Relationship Between Left Atrium Reservoir Strain and One-Year Mortality After Surgery in Patients with Severe Primary Mitral Regurgitation Undergoing Mitral Valve Replacement at Haji Adam Malik General Hospital, Medan - Abimanyu, Roni; Ketaren, Andre Pasha; Nasution, Ali Nafiah (CoinReads Media Prima, 2025)
Introduction: Severe primary Mitral Regurgitation (MR) is a public health program that continues to grow. Echocardiography is still a tool to assess the severity and prognostic of mitral valve disease. LASr assessment has the benefit of assessing the prognostic in patients who have undergone mitral valve replacement surgery. This study aimed to determine the relationship between LASr and mortality one year after surgery for severe primary MR undergoing valve replacement surgery Methods: This study is an analytic study with a cross-sectional design on 55 subjects with severe primary MR who met the inclusion and exclusion criteria at Haji Adam Malik General Hospital. LASr was measured before surgery and followed by the incidence of mortality one year after mitral valve replacement surgery. Data were analyzed univarite and bivariate as well by correlation tests to assess the relationship between LASr and one-year mortality in severe primary MR undergoing valve replacement surgery Results: The study subject totaled 55 patients with an average age of 39,35 ± 12,59 years, 28 patients (50.9%) were male and 11 patients (20%) experienced mortality. The main cause of mitral valve abnormalities in this study was rheumatic, namely 39 cases (70.9%). The LASr threshold value was found to be 18.8 (sensitivity: 90.9%; specificity: 70.5%). (AUC: 0.851; P = 0.0001 and 95% CI (0.751 – 0.952). Conclusion: LASr has a significant correlation to predict one-year mortality in patients with severe primary mitral regurgitation undergoing mitral valve replacement surgery.